Gynecological involvement in eosinophilic granulomatosis with polyangiitis. (2nd February 2016) - Sukhdeo, Aishwarya; Bertouch, James
Abstract: Gynceological involvement in antineutrophil cytoplasmic antibody (ANCA)‐associated vasculitides is rare. We describe a case of ANCA‐associated vasculitis in an elderly woman presenting with fevers, cough and a rash. Further investigations revealed vasculitic involvement of the ovaries, fallopian tubes, uterus and omentum with an eosinophil‐rich infiltrate.